A Platform of Constructivist Learning in Practice: Computer Literacy Integrated into Elementary School - Garcia, Ivan; Pacheco, Carla; Garcia, Gabriel (International Journal of Emerging Technologies in Learning (iJET), 2010)
In Mexico, the conventional teaching approach, when applied specifically to elementary school, seems to fall short of attaining the overall quality objective. The main consequence of this problem is when teachers are not sure that their students really understand the dynamic nature of concepts and mechanism since an early age, particularly in elementary school. This paper presents a pedagogical/technological platform, based on constructivism ideas, as a means of making the learning process in elementary school more efficient and interesting. The constructivist platform presented here uses graphical simulators developed for Web 2.0 as a support tool, creating a teaching and learning environment in which practical experiments can be undertaken as each topic is introduced and explained.